"You're dealing with the bottom here..." understanding reasons for reduced utilisation: a qualitative study on colorectal cancer screening among vulnerable men at a drop-in centre in Denmark - Camilla Rahr Tatari; Pia Kirkegaard; Berit Andersen (BMC, 2024)
Abstract Background Colorectal cancer (CRC) screening can reduce both CRC incidence and mortality, and faecal immunochemical testing (FIT)-based screening programmes are therefore now being implemented in many countries. However, social inequality in FIT-based screening participation is well documented, and initiatives to address this challenge are understudied. We explored the perceptions of CRC screening and the perceived barriers and facilitators towards FIT-based CRC screening among men visiting a drop-in centre for people with severe social problems in Denmark. Methods The study was a qualitative interview study. Participants were sixteen men visiting a drop-in centre in Denmark. A local staff member provided supplementary information and assisted with the recruitment process. The interviews were transcribed verbatim, followed by an inductive content analysis. Results The men were often dealing with health and social problems, and they often had low self-esteem. At first, they stated that they did not think much about cancer and their own risk of being diagnosed with it. They argued that they had little time, energy, and resources to participating in, for example, CRC screening programmes, and barriers to participating were facts of life such as comorbidity and cognitive difficulties. Further, they were not sure how to participate, and some misunderstood the concept of screening. However, during the interviews, the main part of the participants became very keen to participate, and they suggested that in the future, they could receive regular information about cancer screening in face-to-face interactions with someone who cared and was interested in helping them. Conclusion Men in a vulnerable position visiting a drop-in centre were interested in CRC screening. If we intervene in a way that meets the needs among these vulnerable citizens, it may contribute to reducing social inequality in FIT-based CRC screening programmes.